Kelengkapan Resume Medis dan Kesesuaian Penulisan Diagnosis Berdasarkan ICD-10 Sebelum dan Sesudah JKN di RSU Bahteramas - Mangentang, Fera Retno (UI Scholars Hub, 2015)
Medical resume is the summary of the whole medical treatment and care provided by medical doctor to patient. Completeness of medical resume is the reflection of the quality of medical record and serives provided by hospital. Diagnostic must be completely written in accordance with ICD-10. This research used mix method, with cross sectional quantitative method to find out the relation between the characteristic of medical doctor with the completeness of the medical resume and compliance with the diagnostic guidelines based on ICD-10. Result of the research proved that there is a relation between the characteristic of medical doctor with the completeness of the medical resume and compliance with diagnstic guidelines based on ICD-10. Hospital must applied Hospital Management Information System (HMIS) to fasten accurate filling of the medical records, including medical resume.